Diagnosis and Management of Cancer Risk in the Gastrointestinal Hamartomatous Polyposis Syndromes: Recommendations From the US Multi-Society Task Force on Colorectal Cancer. (26th June 2022) - Boland, C. Richard; Idos, Gregory E.; Durno, Carol; Giardiello, Francis M.; Anderson, Joseph C.; Burke, Carol A.; Dominitz, Jason A.; Gross, Seth; Gupta, Samir; Jacobson, Brian C.; Patel, Swati G.; Shaukat, Aasma; et al.
Abstract : The gastrointestinal hamartomatous polyposis syndromes are rare, autosomal dominant disorders associated with an increased risk of benign and malignant intestinal and extraintestinal tumors. They include Peutz-Jeghers syndrome, juvenile polyposis syndrome, the PTEN hamartoma tumor syndrome (including Cowden's syndrome and Bannayan-Riley-Ruvalcaba syndrome), and hereditary mixed polyposis syndrome. Diagnoses are based on clinical criteria and, in some cases, confirmed by demonstrating the presence of a germline pathogenic variant. The best understood hamartomatous polyposis syndrome is Peutz-Jeghers syndrome, caused by germline pathogenic variants in the STK11 gene. The management is focused on prevention of bleeding and mechanical obstruction of the small bowel by polyps and surveillance of organs at increased risk for cancer. Juvenile polyposis syndrome is caused by a germline pathogenic variant in either the SMAD4 or BMPR1A genes, with differing clinical courses. Patients with SMAD4 pathogenic variants may have massive gastric polyposis, which can result in gastrointestinal bleeding and/or protein-losing gastropathy. Patients with SMAD4 mutations usually have the simultaneous occurrence of hereditary hemorrhagic telangiectasia (juvenile polyposis syndrome–hereditary hemorrhagic telangiectasia overlap syndrome) that can result in epistaxis, gastrointestinal bleeding from mucocutaneous telangiectasias, and arteriovenous malformations. Germline pathogenic variants in the PTEN gene cause overlapping clinical phenotypes (known as the PTEN hamartoma tumor syndromes), including Cowden's syndrome and related disorders that are associated with an increased risk of gastrointestinal and colonic polyposis, colon cancer, and other extraintestinal manifestations and cancers. Due to the relative rarity of the hamartomatous polyposis syndromes, recommendations for management are based on few studies. This US Multi-Society Task Force on Colorectal Cancer consensus statement summarizes the clinical features, assesses the current literature, and provides guidance for diagnosis, assessment, and management of patients with the hamartomatous polyposis syndromes, with a focus on endoscopic management.